Nonequilibrium model of water generation in Aircraft Fuel Tanks - Lei Shao; Wenju Yang; Bohan Chen; Jiawei He; Jingxin Tan; Jiahao Yang (Case Studies in Thermal Engineering, 2023)
To investigate the formation of water contaminants in fuel tanks, a nonequilibrium model based on heat and mass transfer is established, and the dissolved water, suspended water, condensed water, free water are analyzed under different conditions. The results show that: With the increase in the heat transfer time constant between fuel and ullage, the volume of condensed water and free water will reach its maximum. The largest volume of free water calculated in this research occurs when the heat transfer time constant between fuel and ullage is equal to 1 ms−1 and 0.8889 L of free water are produced. The time constant of condensation has a similar effect on the volume of condensed and free water as the heat transfer time constant between fuel and ullage. Compared with the effect of the heat transfer time constant between fuel and ullage, the volume change of condensed water and free water is smaller. When the time constants are less than 1 ms−1, the volumes of suspended water, condensate water, and free water increase obviously with the increase of the time constants, and the volume of dissolved water decreases gradually, but these phenomena become less obvious after the time constants increase to 1 ms−1.